PrEP stigma among current and non-current PrEP users in Thailand: A comparison between hospital and key population-led health service settings - Chautrakarn, Sineenart; Rayanakorn, Ajaree; Intawong, Kannikar; Chariyalertsak, Chonlisa; Khemngern, Porntip; Stonington, Scott; Chariyalertsak, Suwat (Frontiers in Public Health, 2022)
Background: HIV Pre-exposure prophylaxis (PrEP) has demonstrated effectiveness in high-risk populations. PrEP service in Thailand became free of charge under the Universal Health Coverage (UHC) in 2021. The National Health Security Office launched a pilot project in 2020 to ensure sustainable service delivery, and the national monitoring and evaluation (M&E) framework was adopted to evaluate early phase implementation. We carried out a cross-sectional survey as part of the M&E process to investigate PrEP stigma among current and non-current PrEP users from both hospital and Key Population Led Health Services (KPLHS) settings in Thailand. Methods: Between August and October 2020, an online cross-sectional survey was conducted. A link for a self-administered questionnaire was distributed to all active PrEP centers and PrEP clients were then recruited by PrEP providers. Descriptive and univariate analysis using Chi-square were applied in the analyses. Attitudes toward PrEP were ranked from the most negative to the most positive. The negative attitude can be interpreted as PrEP stigma. Results: This study included 513 PrEP clients (355 from hospitals and 158 from KPLHS). In both settings, respondents' attitudes toward PrEP were generally positive, but some potential stigma was observed. 31.8% of hospital PrEP clients and 9.5% of KPLHS clients agreed that PrEP users should keep their pills hidden from others. Almost half (44.5%) of hospital clients and 18.4% of KPLHS clients agreed that PrEP users are often viewed negatively by society. More than 20% of hospital clients and 12% of KPLHS agreed that PrEP users frequently experience difficulties when their partner/lover/family find out that he or she is on PrEP. Respondents from the hospitals had slightly higher PrEP stigma than those from KPLHS. Conclusions: According to our findings, at the policy level, the campaign to provide PrEP education to all groups of people should be continued in order to promote a positive view of PrEP and reduce PrEP-related stigma among the general population, which is critical for successful PrEP implementation.